The Emergence of a Networking Primitive in Wireless Sensor Networks. - Levis, Philip; Brewer, Eric; Culler, David; Gay, David; Madden, Sam; Patel, Neil; Polastre, Joe; Shenker, Scott; Szewczyk, Robert; Woo, Alec (Communications of the ACM, 2008)
The wireless sensor network community approached networking abstractions as an open question, allowing answers to emerge with time and experience. The Trickle algorithm has become a basic mechanism used in numerous protocols and systems. Trickle brings nodes to eventual consistency quickly and efficiently while remaining remarkably robust to variations in network density, topology, and dynamics. Instead of flooding a network with packets, Trickle uses a "polite gossip" policy to control send rates so each node hears just enough packets to stay consistent. This simple mechanism enables Trickle to scale to 1000-fold changes in network density, reach consistency in seconds, and require only a few bytes of state yet impose a maintenance cost of a few sends an hour. Originally designed for disseminating new code, experience has shown Trickle to have much broader applicability, including route maintenance and neighbor discovery. This paper provides an over- view of the research challenges wireless sensor networks face, describes the Trickle algorithm, and outlines several ways it is used today.